Misi Dan Keteladanan Perempuan dalam Kisah Para Rasul 16:13-40: Perspektif Gereja Masa Kini - Margaretha Pasau; Roberth Ruland Marini; Nelly Nelly (Phronesis: Jurnal Teologi dan Misi, 2025)
This study examines the mission and role model of women in Acts 16:13–40, with a particular focus on the figure of Lydia and her relevance to the contemporary Church. Lydia’s role as a follower of Christ and a leader of the Christian community in Philippi illustrates that women have made significant contributions to the spread of the Gospel and the development of the early Church. The aim of this research is to explore how Lydia’s missional values and exemplary leadership can be applied within the context of women’s ministry and leadership in the modern Church. This study employs a descriptive qualitative methodology, incorporating narrative analysis of biblical texts alongside a review of contemporary theological literature. The findings indicate that women’s involvement in mission is vital to the growth of the Church, both historically and in the present day. The discussion highlights the challenges and opportunities faced by women in Church ministry, as well as strategies for empowering them in mission and leadership roles. This research offers a fresh perspective on the role of women in contemporary Church missions.